ANALISIS LAPORAN KEUANGAN ARUS KAS PADA PT BNI PERSERO TBK - Rahmat Arapi; Natalia Reyne Lumentah (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
The aim of this research to determine the ratio of liquidity, solvency ratio, investment ratio and cash flow return ratio based on cash flow statement at PT BNI persero Tbk. Data were collected using documentation techniques. In this technique the data obtained by accessing through the internet then download the data on the official website of Indonesia stock exchange (ISE) in the form of financial data in 2011-2015. To the determine the level of liquidity in PT BNI Persero, Tbk is measured using the liquidity ratio. The company’s ability to pay off its long-term debt is measured using a solvency ratio. To determine the the ability of the company to meet the needs of investment ratio. Cash turnover is measured using a cash flow return ratio. The result show that: (1) the liquidity of PT BNI persero Tbk is quite good because the company has sufficient cash availability to meet its short-term liabilities. (2) the solvency is good because it shows the highest ratio compared to the ratio of the last five years. (3) there is a large scale investment in 2013 which resulted in the flow of cash use is greater than the cash generated. This is what causes the financial condition to deteriorate in 2013 in term of investment ratio. (4) The cash flow return ratio shows a good cash flow, judging from the ratio of which most of the figures show the highest if done comparison over the last five years.